Crystal structure of the hydrogen storage active high entropy phase Tb0.82Sm0.18Ni0.83Co0.17Mg - Pavlyuk Nazar; Kordan Vasyl; Dmytriv Grygoriy; Pavlyuk Volodymyr (Zeitschrift für Kristallographie - New Crystal Structures)
Tb0.82Sm0.18Ni0.83Co0.17Mg, orthorhombic, Cmcm (no. 63), a = 3.6707(4) Å, b = 17.723(1) Å, c = 3.9863(4) Å, V = 259.33 (4) Å3, Z = 4, R gt(F) = 0.0334, wR ref(F 2) = 0.0861, T = 293 (2) K.